Benjamin Franklin - Mara, Wil. (New York : Children's Press, 2007)
Briefly introduces the life of Benjamin Franklin, touching on his inventions and his contributions to the city of Philadelphia as well as to the newly formed United States of America.
Includes index.
3.0
K-3
Keywords: Franklin, Benjamin, -- 1706-1790 -- Juvenile literature; Franklin, Benjamin, -- 1706-1790.; Franklin, Benjamin, -- 1706-1790.; Statesmen -- United States -- Biography -- Juvenile literature; Scientists -- United States -- Biography -- Juvenile literature; Inventors -- United States -- Biography -- Juvenile literature; Printers -- United States -- Biography -- Juvenile literature; Statesmen; Scientists; Inventors; Printers; Statesmen -- Biography; Scientists -- Biography; Inventors -- Biography; Printers -- Biography; Statesmen -- United States -- Biography; Inventors -- Biography